Feline sporotrichosis: Case report - Guimarães, Ticiana Machado; Guimarães, André Barreto (Pubvet, 2022)
Feline sporotrichosis is a subcutaneous mycosis of subacute and chronic evolution, whose etiologic agent is a dimorphic and geophilic fungus of the Sporothrix complex (Sporothrix schenckii). Zoonotic transmission has been highlighted, with domestic felines playing an important epidemiological role in the spread of the disease. Despite being a zoonosis, there are few case reports of sporotrichosis in northeastern Brazil. This article aims to describe and report cases of feline sporotrichosis in two cats seen at the Mascot Pet veterinary office, alerting veterinarians to this possible diagnosis. Both had ulcerative skin lesions, one of them having crusts and small hyperemic papules. Imprint cytology of slides was performed in the office and the microscopy technique with Romanowsky staining was performed by the veterinary laboratory Vetinlab, in Bahia, through which yeast-like structures compatible with the agent Sporothrix schenckii were observed. One of the animals was successfully treated with Itraconazole 50mg/animal every 24 hours for a period of four months. However, euthanasia was necessary in one of the cats, performed by the zoonoses control center in Salvador, Bahia.